Transfer of the Dual Orexin Receptor Antagonist Daridorexant into Breast Milk of Healthy Lactating Women - Kaufmann, Priska; Muehlan, Clemens; Anliker‐Ort, Marion; Sabattini, Giancarlo; Siebers, Nicholas; Dingemanse, Jasper (Journal of clinical pharmacology, 2024)
The novel dual orexin receptor antagonist daridorexant was approved in 2022 for the treatment of adult patients with insomnia. The aim of this post‐marketing study was to measure daridorexant and its major metabolites in breast milk and plasma of 10 healthy lactating subjects. This single‐center, open‐label study evaluated the transfer of the analytes into breast milk. A single dose of 50 mg was orally administered in the morning. Milk and blood samples were collected pre‐dose and over a period of 72 h after dosing. The pharmacokinetics of daridorexant in milk and plasma were assessed including the cumulative amount and fraction of dose excreted, daily infant dose, and relative infant dose. Safety and tolerability were also investigated. All subjects completed the study. Daridorexant was rapidly absorbed into and distributed from plasma. Daridorexant and its major metabolites were measurable in breast milk. The cumulative total amount of daridorexant excreted over 72 h was 0.010 mg, which corresponds to 0.02% of the maternal dose. This corresponds to a mean daily infant dose of 0.009 mg/day and a relative infant dose of less than 0.22% over 24 h. The maternal safety profile was similar to that observed in previous studies. Low amounts of daridorexant and its metabolites were detected in the breast milk of healthy lactating women. Since the exposure and potential effects on the breastfed infant are unknown, a risk of somnolence or other depressant effects cannot be excluded.